2015
DOI: 10.3329/jdmc.v22i2.21544
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow trephine biopsy in Haematological diseases: a study of 53 cases

Abstract: Abstract:Bone marrow aspiration (BMA) and biopsy (BMTB)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
1
0
0
Order By: Relevance
“…The diagnosis accuracy of BMA in our study was 84.09% which was similar to the study done by parajuli et al (6). Diagnosis accuracy of BMA was slightly lower in the study done by Smita Chandra et al (77.5%) (8) Our study showed trephine biopsy was also superior to BMA in diagnosing hypoplastic/ aplastic anemia similar to study by parajuli et al (4) and Gupta N et al (9) We encountered a single case of NHL infiltrating the bone marrow which was diagnosed both on BMA and BMB, where as in the study done by vidisha et al (7) much of the cases could not be diagnose on the BMA alone, which stressed out point that both aspiration and biopsy should be done in case of suspected NHL.(7). 2 out of 3(66%) Metastatic carcinoma were diagnosed on bone marrow aspiration which are as similar to the study done by Smita Chandra (8).…”
Section: Resultsupporting
confidence: 87%
“…The diagnosis accuracy of BMA in our study was 84.09% which was similar to the study done by parajuli et al (6). Diagnosis accuracy of BMA was slightly lower in the study done by Smita Chandra et al (77.5%) (8) Our study showed trephine biopsy was also superior to BMA in diagnosing hypoplastic/ aplastic anemia similar to study by parajuli et al (4) and Gupta N et al (9) We encountered a single case of NHL infiltrating the bone marrow which was diagnosed both on BMA and BMB, where as in the study done by vidisha et al (7) much of the cases could not be diagnose on the BMA alone, which stressed out point that both aspiration and biopsy should be done in case of suspected NHL.(7). 2 out of 3(66%) Metastatic carcinoma were diagnosed on bone marrow aspiration which are as similar to the study done by Smita Chandra (8).…”
Section: Resultsupporting
confidence: 87%